Ion upflow and downflow at the topside ionosphere observed by the EISCAT VHF radar - Endo, M.; Fujii, R.; Ogawa, Y.; Buchert, S. C.; Nozawa, S.; Watanabe, S.; Yoshida, N. (CCSD, 2000)
International audience We have determined the MLT distribution and K P dependence of the ion upflow and downflow of the thermal bulk oxygen ion population based on a data analysis using the EISCAT VHF radar CP-7 data obtained at Tromsø during the period between 1990 and 1996: (1) both ion upflow and downflow events can be observed at any local time (MLT), irrespective of dayside and nightside, and under any magnetic disturbance level, irrespective of quiet and disturbed levels; (2) these upflow and downflow events are more frequently observed in the nightside than in the dayside; (3) the upflow events are more frequently observed than the downflow events at any local time except midnight and at any K P level and the difference of the occurrence frequencies between the upflow and downflow events is smaller around midnight; and (4) the occurrence frequencies of both the ion upflow and downflow events appear to increase with increasing K P level, while the occurrence frequency of the downflow appears to stop increasing at some K P level.